건식 및 습식 염소가스 환경에서 노출된 반도체 공정용 316L 스테인리스강의 부식 특성 평가 - 정우철; Woo-chul Jung; 한덕현; Deokhyun Han; 공만식; Man-sik Kong (Corrosion science and technology, 2025)
This study investigated corrosion behavior of 316L stainless steel exposed to chlorine gas (Cl 2 gas) in dry and wet environments at room temperature. Experiments were conducted over 14 days using both electropolished and non-electropolished specimens to evaluate effects of surface treatment and environmental conditions on corrosion. The extent of corrosion was evaluated by measuring weight change and corrosion rate (mm/year). Surface morphology, cross-section almorphology, and corrosion layer were analyzed using SEM/EDS mapping. The non-electropolished specimens formed a corrosion layer more than 7 μm thick, composed of Fe, Cr, Cl, and O. Electropolished specimens maintained a pristine surface with no formation of a corrosion layer. Weight measurements indicated that non-electropolished specimens experienced a weight change of 5.44 mg/㎠ in wet conditions, which was over four times higher than that observed in dry conditions. In contrast, electropolished specimens demonstrated exceptional corrosion resistance due to a stable Cr oxide layer, showing a minimal weight change of less than 0.01 mg/㎠ regardless of moisture presence.